Outcomes of the Rotating Hinge Knee in Revision Total Knee Arthroplasty: A Short-term Report with a Median Follow-up of 2.75 Years in a Large Asian Institute - Dorjiee, Gem; Hirunyachoke, Paphon; Nakbunnam, Rapeepat; Chareancholvanich, Keerati; Pornrattanamaneewong, Chaturong (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: Revision total knee arthroplasty (TKA) is often necessary because of infection and malalignment and represents significantly greater challenges. Rotating-hinge knee (RHK) play an important role in complex situations, with survival rates varying from 73% to 97.2% over 5 to 10 years. However, most knee arthroplasty concepts are primarily tailored to suit Caucasians, potentially raising concerns about their suitability for Asian populations. The purpose of our research was to determine the rates of survival and complications, as well as to review the factors that contribute to failed RHK revisions in our large Asian institute. Methods: This retrospective study included all revisions with RHKs performed between January 2013 and December 2021 while excluding those who underwent primary RHK procedures. Data collection included revision diagnoses and reasons for RHK implant failure. Implant survivorship was calculated from the date of surgery to the time of re-revision surgery. Results: This study included 37 patients, consisting of four men and 33 women participants, with an average age of 75 years. The mean follow-up was 2.75 years. The main causes of revision to RHK were prosthetic joint infection and instability, both accounting for 29.7% of cases, followed by aseptic loosening at 21.6%. The 2-year survival rate was 91.67%. The mean survival time was 2.08 years, with an overall failure rate of 5.4% due to infection. Conclusions: RHK implants are essential in revision knee arthroplasty under specific conditions. Our large Asian institution has shown a 2-year survival rate of 91.67% and a recurrence-free survival rate of 94.6%.